An adventure through thought, philosophy and childhood (2022)
This article presents the results of the project "Pedagogical look at logical thinking in childhood", which is part of the research group Aión: Tiempo de Infancia, of the Universidad Pedagógica y Tecnológica de Colombia. The objective was to promote logical thinking in students from five to six years of age in the transition grade of the Escuela Normal Superior Santiago de Tunja. A documentary compilation was carried out that evidenced the importance of working on logical thinking in the classroom in the early education grades, which contributes to the development of thinking skills. The methodology used was action research, under the qualitative approach, with descriptive design. The study was developed in five phases. For the analysis of results, ATLAS.TI software was used to detail textual coding and to configure semantic networks that graph the relationships between codes and categories. It is concluded that logical thinking, from a philosophical perspective, promotes skills in children that contribute to reflection, argumentation and justification.